2006
DOI: 10.1080/08880010500457939
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Fvii Substitution in a Preterm Infant With Severe Gastrointestinal Bleeding and Fvii Deficiency Due to a Homozygous Donor Splice Mutation Ivs4+1g→A

Abstract: Congenital FVII deficiency is a rare bleeding disorder. Clinical complications are similar to those seen in hemophilia A, and an increased incidence of intracerebral hemorrhage related to birth trauma has been reported. The authors report on an infant who presented at the second day of life with melaena and hematemesis caused by congenital FVII deficiency with minimal activity of 4%. A homozygous mutation IVS4+G-->A, formerly described in 2 siblings, who died of brain hemorrhage within the first month of life,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Prophylaxis should, therefore, be proposed (possibly within the frame of a prenatal diagnosis program) to those families who already have an affected child bearing a "null" F7 gene lesion associated with severe bleeding. 35,36 In addition, early prophylaxis should be started in severely affected children when central nervous system and gastrointestinal bleeding episodes occur. We have recently published a paper on the treatment of "spontaneous" bleeding episodes in FVII deficiency and found that "on-demand" treatment of these severe bleeds is a suboptimal therapeutic choice.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis should, therefore, be proposed (possibly within the frame of a prenatal diagnosis program) to those families who already have an affected child bearing a "null" F7 gene lesion associated with severe bleeding. 35,36 In addition, early prophylaxis should be started in severely affected children when central nervous system and gastrointestinal bleeding episodes occur. We have recently published a paper on the treatment of "spontaneous" bleeding episodes in FVII deficiency and found that "on-demand" treatment of these severe bleeds is a suboptimal therapeutic choice.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term prophylaxis There are 12 case series totalling 31 patients [57,60–70]. Three patients received a PCC [63,67,70], nine received FFP [57,62,69], 10 received FVII concentrate [63,65–67,69,70] and 20 were given rFVIIa [60,61,63–65,67,68,70]. No inhibitor development or thrombotic complications were reported with any product.…”
mentioning
confidence: 99%
“…One hundred forty-eight articles were found. An accurate selection of all these papers (based on titles, abstract and reading in some cases) identified 16 case stories/series and one review about long-term prophylaxis in FVII deficiency published between 1995 and 2014 [9,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Table 1 summarizes patients characteristics and specific prophylactic regimens.…”
Section: Resultsmentioning
confidence: 99%
“…Few data are available in the literature regarding long-term prophylaxis in FVII deficiency. The current review of the literature retrieved data regarding 74 patients, treated with regimens that were highly heter-ogeneous [9,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The indication for long-term prophylaxis was predominantly CNS bleeding followed by haemarthrosis and GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation